ANALISIS PEMBIAYAAN MURABAHAH PADA BSM: PERSPEKTIF MAQASID AL-SHARIAH - Didi Suardi (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2019)
This research attepts to exmine the concept of maqoshid al-Syariah in Islamic jurisprudence in order to highlight its contribution in to more comprehensive, rational, and realistic answers to contemporary financial issues and to thereby increase awareness of the maqoshid approach in structuring and developing Islamic banking products. For this purpose, the article examines the product of murabahah schema in Bank Syariah Mandiri (BSM) branch of Cileduk in order to assess the implementation of this product whether complies with the maqoshid or not. The findings of this reseash are murabahah financing of Bank Syariah mandiri does not yet comply with maqoshid al-Syariah. The second results is the process of murahabah financing in this bank is conducted by transferring the cash money to clients in order to present flexibility, efeciency, and to reduce the tax of financing. This means the BSM implementating murabahah li al –amir bi alshir’a model in its financing.